Evaluasi Kinerja Kontraktor Dalam Proyek Jalan Setapak Masyarakat - Hamisi, Rustam; Hi. Muhammad, Amiruddin; Adjam, Idhar (Peneliti.net, 2025)
One of the physical development programs implemented in Mafututu Village in the 2024 Fiscal Year is the Footpath Construction Project. This project is funded through the Mafututu Village Budget Implementation Document (DPA) as part of efforts to improve accessibility and mobility for communities in coastal areas. Specifically, this project was entrusted to the implementing contractor CV. Mafututu Indah with a total contract value of IDR 119,895,457.29 (One Hundred Nineteen Million Eight Hundred Ninety-Five Thousand Four Hundred Fifty-Seven Rupiah Twenty-Nine Sen). In accordance with the Work Agreement Letter (SPK), the project implementation period is set at ninety (90) calendar days, starting from the issuance of the Work Commencement Order (SPMK), with the aim of ensuring that the construction of this footpath is completed on time and can be immediately utilized by the residents of Mafututu Village. The research method used was quantitative descriptive with a case study approach on the Footpath Construction Project in Mafututu Village. Primary data was collected through field observations and interviews with respondents from the Public Works Agency, project owners, workers, the village government, and the community. The performance variables measured included quality (work quality) and cost (budget efficiency).